Deep insights into the green nitrogen removal by anammox in four full-scale WWTPs treating landfill leachate based on 16S rRNA gene and transcripts by 16S rRNA high-throughput sequencing. (10th December 2020) - Yang, Yuchun; Li, Meng; Hu, Zhong; Shim, Hojae; Lin, Jih-Gaw; Li, Xiao-Yan; Gu, Ji-Dong
Abstract: Inoculation of anaerobic ammonium oxidation (anammox) bacteria-enriched pellets into the full-scale conventional wastewater treatment plants (WWTPs) treating landfill leachate is an effective and economical way to achieve the engineering application of anammox, a green nitrogen removal process. Current knowledge of the active members in the microbial communities of these WWTPs with active anammox granulation remains limited. In this study, the overall microbial communities in these four WWTPs treating landfill-leachate were analyzed using 16S rRNA gene high-throughput sequencing. At the same time, transcriptionally active groups in these aeration tanks, which were inoculated with exogenous anammox pellets were delineated by the reverse-transcribed 16S rRNA sequencing. Anammox bacteria and nitrifiers were enriched in the aeration tanks benefited from the high ammonium inputs, and the significant accumulation of the slow-growing anammox bacteria was positively related to the biomass immobilization on surfaces of carrier materials. In total, 8610 operational taxonomic units (OTUs) were observed in the four aeration tanks and only 29.0% of all OTUs were transcriptionally active, but the percentage of transcriptionally active members in the 1004 core OTUs (OTUs observed in all aeration tanks) were up to 62.2%. Only 11.6% of all OTUs were the core, but they accounted for up to 67.4% of the total DNA reads. The core microorganisms in the aeration tanks tended to be more abundant and active than the others in the community. Some inactive heterotrophic microbes were also detected with dominance in the microbial communities of the aeration tanks, likely from the dead cells and microbial migrations from influent, suggesting the metabolically functional importance of an organism in the WWTPs cannot be accurately assessed by the relative abundance of taxa based on DNA sequencing. Our findings broaden the current understanding on the active microbial communities of WWTPs for implementing the active anammox process and re-affirm the necessity of differentiating between active and inactive microbial groups in any open ecosystems. Graphical abstract: Image 1 Highlights: Microbial communities in four WWTPs showing active anammox process were analyzed. Biomass immobilization significantly promoted to the accumulation of anammox bacteria for N removal. Active organisms were delineated by the reverse-transcribed 16S rRNA sequencing. Microbial migrations resulted in the dominance of inactive microbes in aeration tanks. Core microbes in aeration tanks tended to be more abundant and active.